Effect of ginsenoside Rh-2 via activation of caspase-3 and Bcl-2-insensitive pathway in ovarian cancer cells - Kim, Jin Hee; Choi, Jae-Sun (Physiological research, 2016)
Ginsenoside has been reported to have therapeutic effects for some types of cancer, but its effect on ovarian cancer cells has not been evaluated. In this study, we monitored the effects of ginsenoside-Rh2 (Rh2) on the inhibition of cell proliferation and the apoptotic process in the ovarian cancer cell line SKOV3 using an MTT assay and TUNEL assay. We found that Rh2 inhibited cell proliferation and significantly induced apoptosis. We confirmed the apoptotic effects of Rh2 using western blot analysis of apoptosis-related proteins. Specifically, the levels of cleaved poly ADP ribose polymerase (PARP) and cleaved caspase-3 significantly increased in SKOV3 cells treated with Rh2. Therefore, Rh2 clearly suppressed the growth of SKOV3 cells in vitro, which was associated with induction of the apoptosis pathway. Moreover, the migration assay showed that Rh2 inhibited the invasive ability of SKOV3 cells. Taken together, our results suggest that Rh2 has anticancer effects in SKOV3 cells through inhibition of cell proliferation and induction of apoptosis. Considering the therapeutic potential of Rh2, more studies should be carried out to facilitate the future application of this natural product as a potential anti-cancer agent.
Keywords: hojení ran; signální transdukce; Signal Transduction; Humans; epitelo-mezenchymální tranzice; Female; nádory vaječníků; Ovarian Neoplasms; lidé; Enzyme Activation; proliferace buněk; Proto-Oncogene Proteins c-bcl-2; Epithelial-Mesenchymal Transition; kaspasa 3; Wound Healing; apoptóza; ženské pohlaví; Caspase 3; ginsenosidy; Cell Proliferation; nádorové buněčné linie; Cell Line, Tumor; Ginsenosides; aktivace enzymů; protoonkogenní proteiny c-bcl-2; Apoptosis